Sufentanil Sublingual Tablet 30 mcg for the Management of Pain Following Abdominal Surgery: A Randomized, Placebo‐Controlled, Phase‐3 Study. Issue 7 (10th February 2017) - Minkowitz, Harold S.; Leiman, David; Melson, Timothy; Singla, Neil; DiDonato, Karen P.; Palmer, Pamela P.
Abstract: Background: Results from a phase‐3, prospective, randomized, double‐blind, placebo‐controlled trial evaluating sufentanil sublingual tablet 30 mcg (SST) for the management of pain after ambulatory abdominal surgery are presented. Methods: Adults with American Society of Anesthesiologists status 1 to 3 scheduled to undergo abdominoplasty, open tension‐free inguinal hernioplasty, or laparoscopic abdominal surgery under general or spinal anesthesia that did not include intrathecal opioids during the operation were eligible. Opioid‐tolerant patients were excluded. The primary endpoint was the time‐weighted summed pain intensity difference to baseline (SPID) over 12 hours. Secondary endpoints included SPID over 24 and 48 hours, total pain relief, and patient and healthcare professional (HCP) global assessments. Results: Overall, 161 patients were randomized to SST ( N = 107) or placebo ( N = 54); pain scores were recorded for up to 48 hours. SPID 12 was higher (greater pain intensity reduction from baseline) in the SST group compared with placebo (25.8 vs. 13.1; P < 0.001, with a difference of 12.7 [95% confidence interval 7.16, 18.23]). In the SST group, a greater proportion of patients and HCPs responded "good" or "excellent" on the global assessments compared with placebo ( P < 0.001 for both). There was a numerically, but not statistically, higher incidence of nausea and headache in the SST group. Conclusions: In patients following abdominal surgery in an ambulatory care setting, SST was an effective opioid analgesic in postoperative pain management. In addition, SST was well tolerated with mild‐to‐moderate side effects, similar to those found in placebo‐treated patients.